Bioremediation potential of biofilm forming multi-metal resistant marine bacterium Pseudomonas chengduensis PPSS-4 isolated from contaminated site of Paradip Port, Odisha - Priyadarshanee, Monika; Das, Surajit (Journal of Earth System Science, 2021)
Biofilm forming and heavy metal resistant marine bacterial strain Pseudomonas chengduensis PPSS-4 was isolated from the contaminated marine sediment of Paradip Port, Odisha, India. The strain showed biofilm formation up to 100 mg/L of multi-metal [Pb(II), Cr(VI), and Cd(II)] supplementation in the culture medium. Scanning electron microscopy (SEM) showed aggregation of rod-shaped cells in the extracellular polymeric substance (EPS) matrix of biofilm. Confocal laser scanning microscopy (CLSM) exhibited a higher nucleic acid to the α -polysaccharide ratio in the biofilm, and the observed thickness was ~21 µm. The metal uptake potential of biofilm culture was higher than planktonic culture both in single and multi-metal solutions. FESEM-EDS analysis revealed the sequestration of multi-metals by bacterial cells and biofilm-EPS. FTIR analysis of bacterial EPS further ensured the interaction of functional groups such as –OH, –NH, and P=O with the metal ions. The maximum removal of Pb, Cr, and Cd by the bacterial biomass was observed at 37°C within 4 h of contact time at pH 6, and 4% salinity for Pb and Cr, and 6% salinity for Cd. The present study revealed that the marine bacterium P. chengduensis PPSS-4 can remove multi-metals, and this bacterium could be efficiently utilized for the remediation of heavy metals in the contaminated environment.